IMPLEMENTASI MEDIA PEMBELAJARAN HERBARIUM KREATIF SISWA DALAM MATERI BAGIAN TUMBUHAN DAN FUNGSINYA IPAS KELAS 4 DI SEKOLAH DASAR - Saputri, Iing Melani; Nuruddin, Muhammad; Dwinata, Anggara (Prodi Pendidikan Guru Sekolah Dasar, 2024)
In learning, especially at elementary school level, this needs to be done provide learning media as an intermediary for delivering material. If this is not done, students will have difficulty understanding the lesson material, especially material related to being proud of the nation. Apart from that, the lack of building students' abilities is related to the limited provision of learning media. Thus, there is a need for renewal and innovation in learning media that is able to preserve the value of love for the Indonesian nation and build students' individual abilities. This research aims to develop Herbarium learning media regarding plant parts and their functions in science learning for class IV elementary schools. This research also aims to determine the development process, media feasibility, and media implementation. In this study, the research subjects is class IV students at SDN Menganto Mojowarno for the 2023/2024 academic year. Data collection techniques for the media development process use field notes, media and material suitability use validation questionnaire sheets, media implementation uses student response questionnaires. The results of this research are available at development process according to the steps in the ADDIE model, namely Analysis, Design (Planning), Develop (Development), Implement (Implementation), and Evaluate (Evaluation). The feasibility of the product which was validated by media expert validators and material experts obtained an average score of 92.25% with very valid criteria and suitable for application to students without improvement. The process of implementing learning media is carried out twice, namely on a small scale and a large scale. The small-scale trial was applied to 6 students by random selection, while the large-scale trial was applied to all class IV students. Thus, the implementation of the Herbarium learning media received a score of 91.25% with very good criteria applied to science and science learning.